LmCYP4G102: An oenocyte-specific cytochrome P450 gene required for cuticular waterproofing in the migratory locust, Locusta migratoria - Yu, Z. T.; Zhang, X. Y.; Wang, Y. W.; Moussian, B.; Zhu, Kun Y.; Li, S.; Ma, E. B.; Zhang, J. Z. (My University, 2016)
Cytochrome P450 superfamily proteins play important roles in detoxification of xenobiotics and during physiological and developmental processes. To contribute to our understanding of this large gene family in insects, we have investigated the function of the cytochrome P450 gene LmCYP4G102 in the migratory locust Locusta migratoria. Suppression of LmCYP4G102 expression by RNA interference (RNAi) does not interfere with moulting but causes rapid loss of body weight - probably due to massive loss of water, and death soon after moulting. Accordingly, maintaining these animals at 90% relative humidity prevented lethality. Consistently, RNAi against LmCYP4G102 provoked a decrease in the content of cuticular alkanes, which as an important fraction of cuticular hydrocarbons have been shown to confer desiccation resistance. In addition, the cuticle of LmCYP4G102- knockdown locusts was fragile and easier deformable than in control animals. Presumably, this phenotype is due to decreased amounts of cuticular water that is reported to modulate cuticle mechanics. Interestingly, LmCYP4G102 was not expressed in the epidermis that produces the cuticle but in the sub-epdiermal hepatocyte-like oenocytes. Together, our results suggest that the oenocyte-specific LmCYP4G102 plays a critical role in the synthesis of cuticular hydrocarbons, which are important for cuticle waterproofing and mechanical stability in L. migratoria
Citation: Yu, Z. T., Zhang, X. Y., Wang, Y. W., Moussian, B., Zhu, K. Y., Li, S., . . . Zhang, J. Z. (2016). LmCYP4G102: An oenocyte-specific cytochrome P450 gene required for cuticular waterproofing in the migratory locust, Locusta migratoria. Scientific Reports, 6, 11. doi:10.1038/srep29980
Keywords: Pyrethroid-Resistant Strain; Drosophila-Melanogaster; Insect Cuticle; P450 Enzymes; Developmental Expression; Mechanical-Properties